Yong Tau Foo Corner / Mas Ayu Othman ... [et al.] - Othman, Mas Ayu; Hussain, Shafinas; Haji Mat, Siti Zurina Hanim; Abd Aziz, Nor Azlina; Bakar, Haslina
Yong Tau Foo Comer is establishing as a product business and its business transactions involved directly to the customers. Yong Tau Foo Comer is registered under the partnership agreement. We were encouraged to enter in this business because of the increasing population from time to time in our country. We will start to operate our business on 1st . January, 2003. We choose ' Yong Tau Foo Comer' as our particular business name because the word itself already shows and states the kind of business that is being carried on. The word ' Yong Tau Foo ' already represents the overview of our own main business activities that selling of Yong Tau Foo food to our customers. Besides that, our corner also provides nutritious and delicious side meals item. We choose Shahab Perdana as our location by looking at our target market, comprehensive infrastructure such as communications network, transportation, competition and the development of that area and also near to the supplier.